Faktor-Faktor Cabaran Yang Dihadapi Oleh Pemaju Hartanah Dalam Pembangunan Rumah Mampu Milik - Ani, Muhamad Tarmymy Che (2022)
The Malaysian government, as with most governments, has made it a policy to develop affordable housing (AH) to cater for the needs of medium to low income groups. However, private property developers have not shown keen interest in constructing AH, resulting in a low and insufficient supply of AH. In view of this, four (4) research objectives were formulated for this study. This research employed a quantitative approach and a questionnaire form was specifically developed based on literature review. The developed questionnaire consisted of queries on the one (1) dependent variable and five (5) independent variables of factors. Study data was analyzed via descriptive analysis and correlation analysis using the Statistical Package for Social Science (SPSS) software. Results of the analyses show that the average index for the three (3) factors of cost, perceived uncertainties, and non-standardized policies and regulations to be ‘neutral’, while for the two (2) factors of lack of support, and supplementary factors, the average index was at the ‘agree’ scale. In terms of correlation analysis, only the one (1) factor of construction of AH by developers with perceived uncertainties, registered a significant value. This result indicates that developers are not keen in constructing AH due to the belief that it would be difficult for low income groups to secure loans or financing as well as not having sufficient.